Availability assessment of mixed hydro and diesel power supply system : a case study : Sierra Leone's Bumbuna hydroelectric project and Kingtom Power Station - Kabia, John Amara (Department of Mechanical Engineering, 2014)
Includes bibliographical references (leaves 79-83).